2011
DOI: 10.1039/c1sm05376k
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of cyclodextrins as a parameter to tune the formation of pseudorotaxanes and micelles supramolecular assemblies. A systematic SANS study

Abstract: We studied the formation of polypseudorotaxanes formed with cyclodextrins (CDs) threading a copolymer chain that forms self-assembled structures in water. The size of the CD cavity was chosen such that it is block selective with respect to the formation of inclusion complexes and therefore in terms of altering the structure of the copolymer self-assemblies in a systematic fashion. Small angle neutron scattering (SANS) experiments provide a direct and clear picture of the shape and interactions of the copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…An alternative mechanism is that the micelle formation is the result of a delicate balance of opposite forces: 40 (1) CD threading stretches the polymer chains, increasing the effective volume fraction of the micelles, minimizing the contact with water, and (2) the gel formation is induced by repulsive interactions, maximizing the contact with water (colloidal glass). Studies have been done to observe the structural elucidation of the polymeric network in its hydrated/non-hydrated states.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative mechanism is that the micelle formation is the result of a delicate balance of opposite forces: 40 (1) CD threading stretches the polymer chains, increasing the effective volume fraction of the micelles, minimizing the contact with water, and (2) the gel formation is induced by repulsive interactions, maximizing the contact with water (colloidal glass). Studies have been done to observe the structural elucidation of the polymeric network in its hydrated/non-hydrated states.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the CD presence enhances the T1107 solubility, and consequently, the phase separation and micelle formation are shifted to higher temperature. Small angle neutron scattering measurements evidenced that at a given temperature, the addition of CD, able to incorporate the hydrophobic block of a copolymer, generates the micellar aggregate rupturing [11,31]. As concerns the DH M values, we observed decreases upon the macrocycle addition (Fig.…”
Section: Calorimetric Experimentsmentioning
confidence: 69%
“…This result agrees with Cosgrove and coworkers [11] and Gaitano et al [12] who found that modified b-CDs disturb the micellar aggregates of linear copolymer. Small angle scattering data on Pluronics/CDs mixtures proved that the solubilization of the hydrophobic copolymer block into the CD cavity opposed to the copolymer self-assembling process [31]. Although CD temperature-induced dethreading was observed for poly(N-isopropylacrylamide)/CDs supramolecular assembly, the thermodynamics of the process was never deeply investigated [34].…”
Section: Temperature Effects On the Cd-t1107 Interactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, as shown in video S1, no aggregation is observed after thorough washing. We infer that CB [7] might form inclusion complex with F108 in a similar fashion as reported for cyclodextrin 61,62 and therefore induce aggregation.…”
Section: Cb[7]-modified Cpsmentioning
confidence: 76%